The SARS-CoV-2 Nucleoprotein Induces Innate Memory in Human Monocytes - Urbán, Patricia; Italiani, Paola; Boraschi, Diana; Gioria, Sabrina (Frontiers in Immunology, 2022)
The interaction of SARS-CoV-2 with the human immune system is at the basis of the positive or negative outcome of the infection. Monocytes and macrophages, which are major innate immune/inflammatory effector cells, are not directly infected by SARS-CoV-2, however they can react to the virus and mount a strong reaction. Whether this first interaction and reaction may bias innate reactivity to re-challenge, a phenomenon known as innate memory, is currently unexplored and may be part of the long-term sequelae of COVID-19. Here, we have tested the capacity of SARS-CoV-2 and some of its proteins to induce innate memory in human monocytes in vitro. Our preliminary results show that the Spike protein subunits S1 and S2 and the entire heat-inactivated virus have no substantial effect. Conversely, monocytes pre-exposed to the nucleocapsid N protein react to subsequent viral or bacterial challenges with an increased production of anti-inflammatory IL-1Ra, a response profile suggesting a milder response to new infections.